2014
DOI: 10.1037/a0034900
|View full text |Cite
|
Sign up to set email alerts
|

Can intonational phrase structure be primed (like syntactic structure)?

Abstract: In three experiments, we investigated whether intonational phrase structure can be primed. In all experiments, participants listened to sentences in which the presence and location of intonational phrase boundaries was manipulated such that the recording either included no intonational phrase boundaries, a boundary in a structurally dispreferred location, in a preferred location, or in both locations. In Experiment 1, participants repeated the sentences to test whether they would reproduce the prosodic structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 41 publications
5
28
0
Order By: Relevance
“…The syntactic level is separate from a single sound-based level of representation that encodes phonology, syllabic structure, and metrical information (which we refer to under the blanket term 'phonological information'). We assume one sound-based level as there is insufficient evidence to discriminate different levels (see Sevald, Dell, and Cole 1995;Tooley, Konopka, and Watson 2014).…”
Section: An Outline Theory Of Syntax and Its Interfaces Based On Strumentioning
confidence: 99%
“…The syntactic level is separate from a single sound-based level of representation that encodes phonology, syllabic structure, and metrical information (which we refer to under the blanket term 'phonological information'). We assume one sound-based level as there is insufficient evidence to discriminate different levels (see Sevald, Dell, and Cole 1995;Tooley, Konopka, and Watson 2014).…”
Section: An Outline Theory Of Syntax and Its Interfaces Based On Strumentioning
confidence: 99%
“…Intriguingly, the ordering of direct object and verb-particle-which also shows somewhat mysterious priming effects-has rhythmic correlates as well (Dehé, 2002). The possibility of rhythmic priming in language has not been widely studied, and the evidence that does exist is mixed: While no evidence has been found for priming of pauses within sentences (Tooley, Konopka, & Watson, 2014, and one study found no evidence of lexical stress priming (Bock & Loebell, 1990, Exp. 3), other work that used tone sequences found rhythmic priming for word lists (Cason & Schön, 2012) and for sentences with matching rhythmic structure (Cason, Astésano, & Schön, 2015). Clearly, more work is needed to determine whether (explicit or implicit) rhythmic structure, or any of the other factors besides syntax in Table 4, is responsible for the priming in each case.…”
Section: Studymentioning
confidence: 99%
“…The syntactic level is separate from a single sound-based level of representation that encodes phonology, syllabic structure, and metrical information (to which we refer using the blanket term "phonological information"). We assume one sound-based level, because there is insufficient evidence to discriminate different levels (see Sevald et al 1995;Tooley et al 2014a).…”
Section: An Outline Theory Of Syntax and Its Interfaces Based On Strumentioning
confidence: 99%